Predictors of success in left bundle branch area pacing with stylet-driven pacing leads: a multicenter investigation - Yu, Ga-In; Kim, Tae-Hoon; Lee, Jung-Myung; Kim, Daehoon; Yu, Hee Tae; Uhm, Jae-Sun; Joung, Boyoung; Pak, Hui-Nam; Lee, Moon-Hyoung (Frontiers in Cardiovascular Medicine, 2024)
Purpose: Although left bundle branch area pacing (LBBAP) is an emerging conduction system pacing modality, it is unclear which parameters predict procedural success and how many implant attempts are acceptable. This study aimed to assess predictors of successful LBBAP, left bundle branch (LBB) capture, and factors associated with the number of LBBAP implant attempts.This retrospective observational multicenter study was conducted in Korea. LBBAP was attempted in 119 patients; 89.3% of patients had bradyarrhythmia (atrioventricular block 82.4%), and 10.7% of patients had heart failure (cardiac resynchronization therapy) indication. Procedural success and electrophysiological and echocardiographic parameters were evaluated.The acute success rate of lead implantation in LBBAP was 95.8% (114 of 119 patients) and that of LBB capture was 82.4% (98 of 119 patients). Fewer implant attempts were associated with LBBAP success (three or fewer vs. over three times, p = 0.014) and LBB capture (three or fewer vs. over three times, p = 0.010). In the multivariate linear regression, the patients with intraventricular conduction delay (IVCD) required a greater number of attempts than those without IVCD (estimates = 2.33 [0.35-4.31], p = 0.02), and the larger the right atrial (RA) size, the more the attempts required for LBBAP lead implantation (estimates = 2.08 [1.20-2.97], p < 0.001).An increase in the number of implant attempts was associated with LBBAP procedural failure and LBB capture failure. The electrocardiographic parameter IVCD and the echocardiographic parameter RA size may predict the procedural complexity and the number of lead implant attempts for LBBAP.